2007
DOI: 10.1016/j.lwt.2005.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-soaking whole pelagic fish in a plant extract on sensory and biochemical changes during subsequent frozen storage

Abstract: Plant extract treatments have largely shown a positive effect on inhibiting the quality loss during the frozen storage of minced and filleted fish products. In the present case, the effect of a plant extract on a whole fish product was checked. For it, whole fresh horse mackerel was soaked in a commercial extract solution during 60 min and then kept frozen up to 12 months at À20 1C. Sampling was carried out on the initial material and at months 1, 3, 5, 7, 9 and 12. Two parallel experiments consisting on untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 36 publications
6
41
0
4
Order By: Relevance
“…It is concluded that, under the present conditions, the presence of the organic to previous research related to horse mackerel chilled storage under traditional flake ice conditions (Aubourg, 2001;Losada et al, 2005). However, as a result of endogenous enzyme activity, an important lipid hydrolysis development has already been detected in horse mackerel muscle during frozen storage (Aubourg and Ugliano, 2002;Lugasi et al, 2007).…”
Section: Quality Loss Assessment By Non-lipid Chemical Indexessupporting
confidence: 44%
See 1 more Smart Citation
“…It is concluded that, under the present conditions, the presence of the organic to previous research related to horse mackerel chilled storage under traditional flake ice conditions (Aubourg, 2001;Losada et al, 2005). However, as a result of endogenous enzyme activity, an important lipid hydrolysis development has already been detected in horse mackerel muscle during frozen storage (Aubourg and Ugliano, 2002;Lugasi et al, 2007).…”
Section: Quality Loss Assessment By Non-lipid Chemical Indexessupporting
confidence: 44%
“…One such abundant mediumfat species in the Northeast Atlantic is horse mackerel (Trachurus trachurus) (FAO, 2007b). Great efforts have been made to enhance its shelf life in the frozen state as whole (Simeonidou et al, 1997;Aubourg and Ugliano, 2002;Lugasi et al, 2007), fillet (Simeonidou et al, 1997;Aubourg et al, 2004) or restructured (Sánchez-Alonso et al, 2007;Pazos et al, 2008;Eymard et al, 2010) fish products. Concerning the horse mackerel chilled storage under traditional flake ice conditions, an important quality loss has been observed relating to microbial, physical, chemical and sensory properties (Smith et al, 1980;Mendes, 1999;Aubourg, 2001;Shigemura et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lehmann and Aubourg (2008) reported a shelf life for filleted horse mackerel of 5 months, while Aubourg et al (2004a) reported a shelf life for whole horse mackerel and filleted horse mackerel stored at -20°C of 5 and 3 months. Lugasi et al (2007) found that dipping whole horse mackerel samples in rosemary extract extended the shelf-life from 5 months to at least 7 months at -20°C, according to sensory results. EO treatment, in combination with freezing and handling practices, provides a means to increase fish product shelf-life.…”
Section: The Shelf Life Of Frozen Chub Mackerelmentioning
confidence: 95%
“…Since synthetic antioxidants have been reported to behave as carcinogen and mutating agents, more attention has been addressed to natural antioxidant addition. Accordingly, recent research has been focused on the employment of endogenous-type antioxidants (namely, tocopherols and organic acids) (Aubourg et al, 2004, Medina et al, 2009, Taheri et al, 2012 or natural antioxidants present in plant extracts (namely, polyphenol compounds) (Stodolnik et al, 2005, Lugasi et al, 2007, Tironi et al, 2010.…”
Section: Introductionmentioning
confidence: 99%